Vocational qualifications in Britain and Europe : theory and practice - Prais, S.J. [Verfasser] (My University, 1991)
"This Note considers three questions bearing on the reform of voactional qualifications in Britain, against the background of changes being introduced by the National Council for Vocational Qualifications. First, in what important respects did Britain need a reformed and centrally-standardised system of vocational qualifications? Secondly, what are the proper criteria for choosing between alternative methods of awarding qualifications? The third question is: in what significant ways do Continental systems of awarding qualifications differ from those now proposed for Britain?" (author's abstract) ((en)) Der Beitrag befasst sich mit der Reform der beruflichen Bildung in Grossbritannien. Dabei wird zunächst der Frage nachgegangen, warum Grossbritannien ein zentral-standarisiertes System von Berufsqualifikationen benötigt. Anschliessend werden die verschiedenen Methoden des Qualifikationserwerbs beurteilt und die continentalen Systeme mit Grossbritannien verglichen. (IAB)
Berufsqualifikationen in Grossbritannien und Europa. Theorie und Praxis
Keywords: G 1.2.3 Qualifikationsentwicklungen; S 2.2.4.1 Prüfungsordnungen; Berufsausbildung; Qualifikationserwerb; Prüfungsordnung; Internationaler Vergleich